Value of Emotional Intelligence in Organisations - Iguchi, Akinori (2005)
Intelligence Quotient (IQ) tests and past academic degrees carry much weight when testing a workforce's ability, especially in recruitment procedures, as they are clearly measurable. However, other kinds of expertise such as interpersonal skills have been said to be one of the fundamental requirements of employees in organisations. This argument has been growing in the managerial field as well as in academic institutions. One of these skills, named as Emotional Intelligence by Mayer et al (1990) for the first time was originated by Edward Lee Thorndike (1920) as "Social Intelligence". It is based on one's own feelings, sensing other's feelings, and the ability to perform at one's best in relationships with others. Although there are limitations, the concept and its importance have been widely recognised.